Kontribusi serta tantangan akibat keterbukaan perdagangan internasional terhadap pertumbuhan dan pembangunan ekonomi Indonesia - Septiana, Yuvi Putri (Maliki Interdisciplinary Journal, 2024)
The development of globalization is driving fundamental changes in the world economic order. For a country with an open economy like Indonesia, trade openness will expand cooperative relations and encourage increased economic growth in the country. Therefore, the literature review method involves collecting data from related literature sources regarding writing problems. This article aims to examine the positive contributions and challenges to Indonesia’s economic growth and development caused by openness to international trade. The success of economic integration between countries in the field of trade makes a positive contribution to Indonesia’s economic growth and development, such as encouraging the flow of foreign capital into the country, encouraging improvements in the quality of human resources, and reducing unemployment. However, despite the many positive contributions, it should also be noted that the transformative impact of trade openness can pose challenges for Indonesia that need to be further elaborated, such as the possibility of a gap in economic benefits between more developed and developing countries which will lead to economic dependence on international markets.